TEACHERS’ NON-VERBAL COMMUNICATION INFLUENCING STUDENTS’ MOTIVATION IN LEARNING ENGLISH FOR THE YOUNG LEARNERS - Istiqamah Istiqamah; Sultan Baa; Samtidar Samtidar (Fakultas Keguruan dan Ilmu Pendidikan, 2023)
This study aimed at finding out the types of teachers’ non-verbal communication in English classes and the types of teachers’ non-verbal communication the most and less affecting young learners’ motivation in English classes. This study applied a mixed-method research design. The participants were two English teachers; the third and fourth-grade students, third grade consisted of 20 students while the fourth grade consisted of 7 students at SDIT At-Tibyan Al-Auliya Bajeng selected by total population sampling. An observation checklist was used to find out the types of teachers’ non-verbal communication in English classes and a questionnaire was used to find out the types of teachers’ non-verbal communication the most and less affecting young learners’ motivation in English classes. The findings of this study showed types of teachers’ non-verbal communication in English classes were divided into two parts they are body languages, which consisted of facial expressions, body gestures and movements, eye contact and touch and the use of space, and paralanguage which consisted of intonation, pitch, rhythm, volume, speed, accent and emphasis and types of teachers' nonverbal communication that most affected young learners’ motivation in English classes was body gesture and movement, based on the result of questionnaire 85% of the students very agree that the teachers' body gesture and movement affected their motivation in learning English, and 15% of them agree that they get more motivation if the teacher uses their body gestures in the learning process, while types of teachers’ non-verbal communication that less affected young learners’ motivation in English classes was touch and the use of space, based on the result of questionnaire only 19% of the students very agree and also 19% of students felt agree that the teachers' body gesture and movement affected students’ motivation in learning English.